PENERAPAN PELAYANAN PEMBUATAN KARTU TANDA PENDUDUK BERBASIS ELECTRONIK (E-KTP) - Oja, Hubertus; Aflaubun, Paskalina; Adryani Moento, Paul (Papsel Journal of Humanities and Policy, 2025)
E-KTP is one of the innovations in population administration services based on electronics. This study aims to analyze the application of electronic-based identity card (E-KTP) making services. The method used is a qualitative method. Data collection techniques through interviews, observations, and documentation. Meanwhile, data analysis uses: data reduction, data presentation, and conclusion drawn. Based on the results of the study, it shows that the service of making an electronic-based identity card (E-KTP) at the Merauke Regency Population and Civil Registration Office has not been maximized in its application. This can be seen from: The creativity of employees in working has been good but has not been maximized, often running out of money in making digital ID cards. The agency has not been able to protect the need for ID card blanks. The new innovation developed, namely the digital population system, is transformed into a smartphone for each individual. . The responsiveness carried out in anticipating every form of change that occurs, both in terms of policies, laws, and community demands in the service of making ID cards at the population and civil registry offices has been running well.